Activated CD4+ T Cells and Highly Differentiated Alloreactive CD4+ T Cells Distinguish Operationally Tolerant Liver Transplantation Recipients. Issue 1 (21st July 2021) - Duizendstra, Aafke A.; de Knegt, Robert J.; Mancham, Shanta; Klepper, Mariska; Roelen, Dave L.; Brand‐Schaaf, Simone H.; Boor, Patrick P.; Doukas, Michail; de Man, Robert A.; Sprengers, Dave; Peppelenbosch, Maikel P.; Betjes, Michiel G. H.; et al.
Abstract : Spontaneous operational tolerance to the allograft develops in a proportion of liver transplantation (LT) recipients weaned off immunosuppressive (IS) drugs. Several studies have investigated whether peripheral blood circulating T cells could play a role in the development or identify operational tolerance, but never characterized alloreactive T cells in detail due to the lack of a marker for these T cells. In this study, we comprehensively investigated phenotypic and functional characteristics of alloreactive circulating T cell subsets in tolerant LT recipients (n = 15) using multiparameter flow cytometry and compared these with LT recipients on IS drugs (n = 23) and healthy individuals (n = 16). Activation‐induced CD137 was used as a marker for alloreactive T cells upon allogenic stimulation. We found that central and effector memory CD4+ T cells were hyporesponsive against donor and third‐party splenocyte stimulation in tolerant LT recipients, whereas an overall hyperresponsiveness was observed in alloreactive terminally differentiated effector memory CD4+ T cells. In addition, elevated percentages of circulating activated T helper cells were observed in these recipients. Lastly, tolerant and control LT recipients did not differ in donor‐specific antibody formation. In conclusion, a combination of circulating hyperresponsive highly differentiated alloreactive CD4+ T cells and circulating activated T helper cells could discriminate tolerant recipients from a larger group of LT recipients. Abstract : https://www.wileyhealthlearning.com/#/online-courses/3669f445-172a-4174-a17b-9487a0828f19